Induction Failure in Acute Leukemia or Parvovirus B19 Infection?. Issue 7 (October 2017) - Tüfekçi, Özlem; Yilmaz Bengoa, Şebnem; Erdem, Melek; Ören, Hale
Abstract : Parvovirus B19 infection may be seen in acute leukemia patients and clinical findings and cytopenia caused by the viral infection may complicate the evaluation of the remission status. Herein we present a standard risk pediatric acute lymphobiastic leukemia patient who developed myalgia, bone pain, bone marrow aplasia and sinusoidal obstruction syndrome at the end of the induction treatment and was diagnosed as having parvovirus B19 infection.